Thyrotoxicosis: an under-recognised aetiology. (20th May 2015) - Dave, Anjalee; Ludlow, Jason; Malaty, John
Abstract : A 53-year-old woman presented for evaluation of dizziness, shortness of breath and chest pain. She was found to be in atrial fibrillation with rapid ventricular response that was determined to be caused by iodine-induced thyrotoxicosis (from a CT scan with intravenous contrast 2 months prior to presentation). Jod-Basedow syndrome (iodine-induced hyperthyroidism) is infrequently considered as a cause of thyrotoxicosis, even when typical risk factors are present. However, this patient did not have typical risk factors: she did not reside in an iodine deficient area, did not have a prior diagnosis of thyroid disorder or goitre, had never been treated with thyroid medications or medications known to cause thyroid dysfunction and she presented later than is typical with this syndrome (2 months after receiving iodinated contrast). She had complete resolution of hyperthyroidism and atrial fibrillation 2 weeks later with no recurrence over the following 7 months.